Prophet of the watchtower an exposition of Habakkuk - Tatford, Frederick Albert, 1901- (Sussex, UK Prophetic Witness, 1973)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Habakkuk -- commentaries